1996
DOI: 10.1055/s-2007-1005580
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience with a New, Partially Covered Wallstent for Malignant Biliary Obstruction

Abstract: Covering biliary metal stents is a potential solution to prevent tissue ingrowth. However, current prototypes need to be improved in order to achieve this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 0 publications
0
45
1
1
Order By: Relevance
“…Subsequently, Gore-Tex, 11 silicone, 24 and polyurethane [25][26][27][28][29][30] were evaluated as materials for the covered membrane. Miyayama et al, using polyurethane covered Gianturco stents, reported that the stent occlusion rate was only 5% due to tumour overgrowth above the stent edge and that no tumour ingrowth was observed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Gore-Tex, 11 silicone, 24 and polyurethane [25][26][27][28][29][30] were evaluated as materials for the covered membrane. Miyayama et al, using polyurethane covered Gianturco stents, reported that the stent occlusion rate was only 5% due to tumour overgrowth above the stent edge and that no tumour ingrowth was observed.…”
mentioning
confidence: 99%
“…26 However, other studies suggested that a covering membrane was not effective in preventing tumour ingrowth and did not improve stent patency. [27][28][29] Hausegger et al, using polyurethane covered Wallstents, reported that the obstruction rate of those covered EMS was 33%, mainly due to tumour ingrowth, concluding that covered EMS were not superior to uncovered EMS. 29 More recently, we published a prospective consecutive study using handmade polyurethane covered Wallstents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extended patency of U-SEMS is associated with several benefits inc1uding: 1) a better quality of life for patients not only because of avoidance ofunnecessary procedures but also due to increased syrnptom-free period [B-IS]; 2) improved survival because it could prevent life-threatening conditions such as acute cholangitis and procedure-related complications [38]; 3) lower costs because of avoidance of repeated ERep. unexpected greater complication rate attributed to migration, cholecystitis and pancreatitis [39,40]. Regardless, the superior effectiveness of both SEMS is offset by significant higher up-front costs compared to PE stents.…”
Section: Research Problems and Objectivesmentioning
confidence: 99%
“…In patients with obstruction at the hilar portion or above, which is difficult to approach using an endoscopic method, percutaneous approaches have a higher rate of success than endoscopic approaches, especially when self-expanding metallic stents are used [8,9]. Stent occlusion due to bile sludge formation and tumor out-and ingrowth interferes with stent patency; therefore, covered metal stents have been introduced to improve the patency and efficacy [5,[10][11][12][13][14]. But, the major concerns that may occur during covered biliary stent placement are biliary complications such as cholecystitis or cholangitis [5,15,16].…”
Section: Introductionmentioning
confidence: 99%